Inovasi Pelayanan Dinas Perpustakaan dan Kearsipan Kota Metro Melalui Program Ebook dalam Upaya Menumbuhkan Minat Baca Remaja - I Made Jaya Muna; Intan Fitri Meutia; Devi Yulianti (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
Reading interest in Indonesia is still relatively low because the number of books in circulation is uneven, and most books are circulated only in big cities. To overcome this, the Metro City Regional Library and Archives Office are in accordance with its vision and mission in utilizing information technology, namely by creating innovations that make libraries attractive through the ebook program. This program is a service innovation provided by the Metro City Regional Library and Archives Service, namely a library based on digital applications that can easily find and read books coming to the library. This study seeks to determine service innovation's application to the Metro City Library and Archives Service through the ebook program and the supporting and inhibiting factors in implementing the ebook program innovation in the Metro City Library and Archives Service. This research is a descriptive study with a qualitative approach. This study indicates that the ebook program innovation carried out by the Metro City Library and Archives Office is quite useful in its application. This can be seen from the fulfillment of four of the six indicators of innovation typology: new or improved services, administrative innovation, system innovation, and radical change. Some things of concern are the innovation carried out still shows conceptual weaknesses because the Metro City Library and Archives Service still carries a Type B library and in the process of making application systems require a long time and maintenance of application systems that must be done regularly by human resources who are competent in their field.